2022
DOI: 10.1186/s13049-022-01015-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluid resuscitation with balanced crystalloids versus normal saline in critically ill patients: a systematic review and meta-analysis

Abstract: Background Intravenous fluids are used commonly for almost all intensive care unit (ICU) patients, especially for patients in need of resuscitation. The selection and use of resuscitation fluids may affect the outcomes of patients; however, the optimal resuscitative fluid remains controversial. Methods We systematically searched PubMed, Embase, and CENTRAL. Studies comparing balanced crystalloids and normal saline in ICU patients were selected. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(32 reference statements)
2
6
0
Order By: Relevance
“…Daily chloride intake was also associated with follow-up eGFR in survivors at 90 days follow-up. Although previous cohort studies comparing liberal and restrictive chloride regimens have shown similar results in relation to patient and renal survival outcomes [ 4 , 7 ], no definite differences in these outcomes have been demonstrated between resuscitation regimens of higher or lower chloride concentrations in RCTs or meta-analyses to date despite solid theoretical background to suggest otherwise [ 1 , 2 , 3 , 5 , 6 , 9 ]. Importantly, no RCT data exist on patient or renal outcomes in relation to chloride intake in critically ill AKI patients receiving CRRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily chloride intake was also associated with follow-up eGFR in survivors at 90 days follow-up. Although previous cohort studies comparing liberal and restrictive chloride regimens have shown similar results in relation to patient and renal survival outcomes [ 4 , 7 ], no definite differences in these outcomes have been demonstrated between resuscitation regimens of higher or lower chloride concentrations in RCTs or meta-analyses to date despite solid theoretical background to suggest otherwise [ 1 , 2 , 3 , 5 , 6 , 9 ]. Importantly, no RCT data exist on patient or renal outcomes in relation to chloride intake in critically ill AKI patients receiving CRRT.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large meta-analysis on the comparison of saline and balanced crystalloids did not demonstrate consistent survival benefits in relation to either solution. However, saline (chloride concentration 154 mmol/L) has shown better results in the treatment of traumatic brain injury, while patients without traumatic brain injury have benefitted more from balanced crystalloids (chloride concentration: Plasma-Lyte 98 mmol/L and Ringer 112 mmol/L) [ 9 ]. Importantly, there are no studies on the effects of chloride intake on patient or renal outcomes in critically ill acute kidney injury (AKI) patients receiving continuous renal replacement therapy (CRRT).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows the preference for balanced crystalloids over NS with avoidance of hyperchloremic acidosis, but a recent meta-analysis of eight studies showed lower mortality in patients with traumatic brain injury (TBI) receiving NS [relative risk (RR): 1.25; 95% confidence interval (CI): 1.02–1.54]. 19 RL being hypotonic in nature should be avoided in TBI. Secondary analysis of prospective, observational, multicenter, major trauma transfusion (PROMMTT) study showed that RL was associated with higher adjusted mortality compared with NS in TBI (HR 1.78; CI: 1.04–3.04; p = 0.035).…”
Section: Discussionmentioning
confidence: 99%
“…Similar overall results were found in two additional systematic reviews with meta-analyses when limiting study inclusion to randomized studies. 41,42 Differences in study design (e.g., blinding, crossover vs. parallel group) is always a consideration when comparing the results of several trials, but there are some particular issues that have been the subject of discussion, particularly in light of the BaSICS and PLUS investigations. A recent publication summarized the more common concerns mentioned by skeptics for the overall lack of statistically significant differences noted between balanced crystalloids and normal saline in the large randomized trials.…”
Section: Crystalloidsmentioning
confidence: 99%